2011
DOI: 10.1007/s10439-011-0353-y
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Glucose Uptake by Ovarian Follicular Cells

Abstract: In vitro maturation (IVM) of mammalian oocytes provides an alternative to traditional in vitro fertilization techniques for clinical treatment of infertility or animal breeding. IVM involves the collection of oocytes from the ovary prior to ovulation, with maturation occurring in a laboratory environment. The success of IVM is highly sensitive to the in vitro nutrient environment. The nurse cells surrounding the oocyte, known as cumulus cells, regulate this environment and removal of these cells reduces the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…In cows that have commenced oestrous cycles, this could potentially affect oestradiol production by follicles as well as progesterone production by corpora lutea. Low blood glucose could potentially compromise a variety of essential metabolic processes in ovarian cells including oocytes that depend on glucose for energy (Clark et al, 2011;Berlinguer et al, 2012). In their recent study of bovine follicles, Walsh et al (2012) concluded that STAR gene expression (the rate limiting enzyme in steroidogenesis) was specifically down-regulated by the metabolic profile found in early lactation (low glucose, insulin and IGF1).…”
Section: Itemmentioning
confidence: 99%
“…In cows that have commenced oestrous cycles, this could potentially affect oestradiol production by follicles as well as progesterone production by corpora lutea. Low blood glucose could potentially compromise a variety of essential metabolic processes in ovarian cells including oocytes that depend on glucose for energy (Clark et al, 2011;Berlinguer et al, 2012). In their recent study of bovine follicles, Walsh et al (2012) concluded that STAR gene expression (the rate limiting enzyme in steroidogenesis) was specifically down-regulated by the metabolic profile found in early lactation (low glucose, insulin and IGF1).…”
Section: Itemmentioning
confidence: 99%
“…However, the spatial and temporal resolution of these methods is not high, and they require cell destruction. On the other hand, given that the intimate interconnection between cumulus cells and the oocyte could be critical for glucose uptake by the oocyte, it is important to include an examination of the live COC as a whole (as opposed to the isolated oocyte) (8). Hence, instead of using an isotope, we here employed a fluorescent glucose derivative (6-NBDG) to directly visualize glucose transport in live mouse COCs.…”
Section: Time Course Of 6-nbdg Uptake In Cocsmentioning
confidence: 99%
“…With the observation that generally static in vitro culture conditions may not provide enough oxygen to the embryo compared with dynamic in vivo conditions where the fluid in the oviduct is mixed during muscle contraction and cilia beating. The structure of this model was similar to a previous model of the immature ovarian follicle, and to more recent models of nutrient availability of the oocyte . The model predicted that diffusion in static culture was sufficient to provide the embryo with the oxygen it requires for development.…”
Section: Postfertilization and Early Embryonic Stagesmentioning
confidence: 67%